2012
DOI: 10.1136/bmjopen-2012-000973
|View full text |Cite
|
Sign up to set email alerts
|

Lung function in volunteers before and after exposure to trichloramine in indoor pool environments and asthma in a cohort of pool workers

Abstract: ObjectivesExposure to trichloramine (NCl3) in indoor swimming-pool environments is known to cause mucous membrane irritation, but if it gives rise to changes in lung function or asthma in adults is not known. (1) We determined lung function in volunteers before and after exposure to indoor pool environments. (2) We studied the occurrence of respiratory symptoms and asthma in a cohort of pool workers.Design/methods/participants(1) We studied two groups of volunteers, 37 previously non-exposed healthy persons an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 21 publications
2
20
1
Order By: Relevance
“…CC-16 levels in serum increase when lung epithelium permeability is adversely affected by air pollutants or other lung toxicants. On the contrary, reduced levels of CC-16 in lung lavage fluid occur in several lung disorders, probably due to a decrease in the production of CC-16 as a consequence of a depletion of Clara cells [79]. In the present study, neither significant increase nor significant decrease was observed in the plasma levels of CC-16 of photocopier operators indicating insignificant effects of the PM on the lung epithelium which is surprising.…”
Section: Discussioncontrasting
confidence: 82%
“…CC-16 levels in serum increase when lung epithelium permeability is adversely affected by air pollutants or other lung toxicants. On the contrary, reduced levels of CC-16 in lung lavage fluid occur in several lung disorders, probably due to a decrease in the production of CC-16 as a consequence of a depletion of Clara cells [79]. In the present study, neither significant increase nor significant decrease was observed in the plasma levels of CC-16 of photocopier operators indicating insignificant effects of the PM on the lung epithelium which is surprising.…”
Section: Discussioncontrasting
confidence: 82%
“…[21] Swimming pool workers have also experienced symptoms associated with the lower respiratory tract and an increased risk of asthma. [22] Trichloramine levels of 100 or 570 mg/m 3 have been associated with work-related asthma in personnel working at indoor swimming pools. [12] Trichloramine exposure and the occurrence of asthma among swimming pool employees have also been described by Rosenman, Millerick-May, and Reilly et al [23] At present, there is no OEL for trichloramine adopted in Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…67,68 Healthy adults have also been shown to have decreases in lung function when exposed to pool air during exercise (0.8% FEV 1 decrease). 69 On biopsy, swimmers have similar inflammatory and remodeling changes as mild asthmatics and increased mucin levels. 70 Belgian researchers have found strong evidence of a relationship between chlorine exposure and asthma, or exercise-induced bronchospasm, in children (for children with high immunoglobulin E, OR 1.79 per 100-hour increase in lifetime pool attendance, CI 1.07-2.72), 71 (OR if children swam as infants 3.0, CI 1.3-7.4 ), 72 (adolescents with highest pool exposure have an OR 3.74, CI 1.40-9.93, population-attributable risk of asthma 63.5% ).…”
Section: Bleachmentioning
confidence: 99%